THE GREAT RUSSIAN SCIENTIST M.V. LOMONOSOV - G.L. Mikirtichan (Педиатрическая фармакология, 2011)
This article presents reflections on the contribution of the great Russian scientist, one of the most prominent world science stars Mikhail Lomonosov (8/19.11.1711–4/15.04.1765) in connection with the 300th anniversary of his birth celebrated in 2011. Particular attention is paid to his role as an advocate for the development of domestic education and science, and his views on medicine. In the same year we are celebrating the 250 years anniversary since M. Lomonosov’s writing the letter to I.I. Shuvalov, «On the saving and reproduction of the Russian People» (1761), which contained an extensive program of increasing the country's population,  which included a range of legal, social and medical measures to help increase fertility and reduce child mortality. Key words: M. V. Lomonosov, I. I. Shuvalov, Moscow University, «On the saving and reproduction of the Russian people». (Pediatric pharmacology. — 2011; 8 (6): 136–140).